Fif's Strategy for Dealing with Problematic Financing in the Post-Pandemic Period - Risqika Yunafiroh; Novi Tri Oktavia (Journal of Nusantara Economy, 2023)
Research This motivated by weakness economy public consequence from impact of Covid-19 that occurred for 2 (two) years so that at risk of occurring financing problem at the institution Finance FIF Tulungagung . Objective he did study This For describes the strategy used by FIF Tulungagung in face financing problem post happening the covid-19 pandemic . The method used by researchers in do study This is approach qualitative with type studies case , where researcher in a manner empirical look for knowledge with investigate phenomenon in context life real with use proof multisource accompanied settlement model data collection financing problem through sources from articles , papers , books , internet sites , results study associated , and sources written other related _ with settlement financing problem at FIF Tulungagung . Research results found _ on- site researcher show that FIF Tulungagung in face financing problem using the reminder strategy via network communication phone to creditors who are experiencing financing problem . If after a creditor reminder process is carried out No give response whatever to FIF Tulungagung _ so billing process is carried out . If deep 30 days time more creditor still No pay the bill is credit status congested raised from billing to remedies. FIF Tulungagung do execution guarantee fiduciary If creditor ignore letter subpoena given by FIF Tulungagung officers at the time visit to House creditor .